Adaptability analysis in niger (Guizotin abyssinicia)* - PATIL, H S PATIL; PATIL, V S (The Indian Journal of Agricultural Sciences, 2011)
Twelve genotypes of niger (Guizotin abyssinicia Cass) were evaluated from 1997-98 to 2003-04 in 8 environments under rainfed conditions for seed yield. The G x E interaction was present. On partitioning of it into linear and non-linear components both were responsible in the inheritance of seed yield in niger. However, the linear component was larger in magnitude. The genotypes, viz ’IGPN 9628’, ’IGPN 9610’ and ’IGPN 9605’ were found to be more responsive and stable. However, the genotypes ’IGPN 9629’ and ’DHL 1 ’ were responsive and stable for poor environmental conditions (below average stability ). The study an correlation among all parameters of stability indicated that the stability parameters appeared to be governed by different gene or genes in combination in niger.